1994
DOI: 10.1139/z94-262
|View full text |Cite
|
Sign up to set email alerts
|

Effects of adult salinity acclimation on larval survival and early development of Strongylocentrotus droebachiensis and Strongylocentrotus pallidus (Echinodermata: Echinoidea)

Abstract: Larval survival and development rates of Strongylocentrotus droebachiensis and Strongylocentrotus pallidus were determined as a function of salinity in two experiments by (i) directly transferring fertilized eggs obtained from adults acclimated to sea water at a salinity of 30‰ to cultures containing seawater at salinities of 30, 27.5, 25, 22.5, 20, 17.5, 15, 12.5, and 10‰ at 10 °C; and (ii) acclimation of adult sea urchins to the salinity–temperature conditions described above for 2, 3, and 4 weeks prior to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 23 publications
2
14
0
Order By: Relevance
“…This effect was unequivocally not genetic since fathers were able to alternate between the production of hyposaline-tolerant spermatozoa and normal sperm depending on the environment in which they lived. In conclusion, gamete plasticity in response to stress, may be a typical characteristic of external fertilizers that release their sperm directly into the environment (e.g., most marine invertebrates, most fish, and amphibians), which is in line with some papers reported in the literature (Adriaenssens, van Damme, Seebacher, & Wilson, 2012;Hintz & Lawrence, 1994;Parker et al, 2012;Roller & Stickle, 1994) and less common in internal fertilizers, but this remains to be tested.…”
Section: Discussionsupporting
confidence: 80%
“…This effect was unequivocally not genetic since fathers were able to alternate between the production of hyposaline-tolerant spermatozoa and normal sperm depending on the environment in which they lived. In conclusion, gamete plasticity in response to stress, may be a typical characteristic of external fertilizers that release their sperm directly into the environment (e.g., most marine invertebrates, most fish, and amphibians), which is in line with some papers reported in the literature (Adriaenssens, van Damme, Seebacher, & Wilson, 2012;Hintz & Lawrence, 1994;Parker et al, 2012;Roller & Stickle, 1994) and less common in internal fertilizers, but this remains to be tested.…”
Section: Discussionsupporting
confidence: 80%
“…Overall, we suspect that the effects we observed here are widespread among marine invertebrates with external fertilizationthere are strong indications that such effects occur in both other species of annelid and in echinoderms and molluscs (Tait, Atapattu & Browne 1984;Hintz & Lawrence 1994;Roller & Stickle 1994;Parker et al 2012), we eagerly await further studies exploring the prevalence of gamete plasticity in this group.…”
Section: O N S E Q U E N C E S O F T R a N S G E N E R A T I O N A mentioning
confidence: 84%
“…Similarly, one study has shown that mothers increase the target size of their eggs to make them more easily fertilized when the local density of males is low and the probability of sperm limitation is high (Crean & Marshall ). Finally, some studies have shown that the negative effects of low salinity on fertilization rates are diminished when adults are first kept in lower salinity conditions (Tait, Atapattu & Browne ; Hintz & Lawrence ; Roller & Stickle ), suggesting that some gamete plasticity has occurred in one or both gamete types but the consequences of this plasticity for later life‐history stages remain unclear. These consequences are particularly important to explore given the increased recognition of the role of both maternal and paternal effects.…”
Section: Introductionmentioning
confidence: 99%
“…The main objective of this study was to determine effects of short-term and developmental acclimation on adult salinity tolerance for a rapidly colonizing species, the copepod Eurytemora affinis. While some studies examined effects of salinity on development rate and tolerance of invertebrates (Roller and Stickle 1994;Walker and Clare 1994;Wright et al 1996), effects of developmental salinity on adult performance or tolerance have rarely been tested.…”
Section: Introductionmentioning
confidence: 99%